Analysis Of Culture-Specific Items in the Arabic Translation Of Herman Melville’s Moby-Dick - Hemza Zeghar; Meriam Benlakdar (Ijaz Arabi Journal of Arabic Learning, 2022)
This paper aims to analyze the translation procedures adopted by Ihsan Abbas in translating culture-specific items in Herman Melville’s novel ‘Moby-Dick.’ This novel has been selected as a case study because of its eminent status within the canon of American literature, its popularity around the world and the nature of its language. Translation procedures used for dealing with each CSI are investigated using a theoretical model that is developed in this study based on models proposed by Aixelá (1996) and Davies (2003). Particular emphasis is placed on displaying the translator’s masterful Arabic translation, his force and exquisite felicity of diction, and how he managed to mitigate some of the insuperable challenges faced in translating culturally embedded references, sea vocabulary, and cetological terms into a language lacking ready equivalents for such highly specialized terminology.